Effectiveness of Pulsed Dye Laser Treatment in Tufted Angioma: A Promising Intervention - Dwiyana RF; Lestari ER; Effendi RMRA; Gondokaryono SP; Diana IA; Usman HA; Suhada KU; Anandita R (Dove Medical Press, 2023)
Reiva Farah Dwiyana,1 Elisabet Risubekti Lestari,1 Raden Mohamad Rendy Ariezal Effendi,1 Srie Prihianti Gondokaryono,1 Inne Arline Diana,1 Hermin Aminah Usman,2 Kamelia Utami Suhada,1 Rafithia Anandita1 1Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital Bandung, West Java, Indonesia; 2Department of Anatomical Pathology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital Bandung, West Java, IndonesiaCorrespondence: Reiva Farah Dwiyana, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, 40161, Indonesia, Tel +62222032426 ext. 3449, Fax +62222032426, Email reiva@unpad.ac.idIntroduction: Tufted angioma (TA) is a rare benign vascular tumor usually occurring in the first year of life. It may present as reddish papules or purplish red to black plaques. Tender lesions commonly affect the neck, upper trunk, and shoulders. Histologic tufts of capillaries infiltrating the dermis in a "cannon ball" distribution pattern confirm the diagnosis. However, effective treatments for TA are scarce. Pulsed dye laser (PDL) is an alternative therapy for TA, particularly concerning cosmetics and pain relief. This case report demonstrates the effectiveness of PDL as a treatment for TA.Case: We report a 15-year-old girl with five-year history of painful purplish red plaques on her left cheek, neck, chest, left shoulder, and back. Histopathological examination from skin biopsy showed discrete "cannon ball" pattern in the dermis. Laboratory examination revealed normal platelet count and fibrinogen level. Based on these presentations, the diagnosis of TA without complications was made. We treated the lesion using 595-nm PDL with 6.5− 10 J/cm2 fluence of, 1.5 ms pulsed duration, and 5− 7 mm spot size every three weeks. Reductions in redness and pain were seen after four sessions of treatment.Discussion: PDL promotes selective vascular damage with minimal injury to the surrounding skin. Capillary tufts in TA could therefore serve as a target for laser treatment, which may result in fading redness and pain reduction.Conclusion: PDL is effective in reducing redness and pain in TA.Keywords: pulse dye laser, tufted angioma, vascular tumor